Factors Affecting Job Satisfaction of Village Officials in West Seluma Sub-District of Seluma Regency - Dwi Kurniawan; Nia Indriasari; Yanto Effendi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The aim of this study is to determine factors such as compensation, job promotion and work environment affecting job satisfaction of village officials in West Seluma Sub-district, Seluma Regency.The sample in this study were 47 village officials in West Seluma Sub-district, Seluma Regency. The sampling technique used in the study was a census because all populations were sampled. Data collection using a questionnaire and the method of analysis used is multiple linear regression, test of determination and hypothesis testing.The results show that a positive regression with the regression equation Y = 0.682 + 0.551X1 + 0.185 X2 + 0.293X3. The coefficient of determination using the R square model. From the results of calculations using SPSS, it can be seen that the coefficient of determination of R square is 0.791. This means that X1 (compensation), X2 (promotion), X3 (work environment) have a contribution to job satisfaction (Y) by 79.1% while the remaining 20.9% is influenced by other variables not examined in thisstudy. Compensation has a significant influence on job satisfaction of village officials in WestBarat Sub-district, Seluma Regency. This illustrates that as compensation increases, the job satisfaction of village officials will also increase. Job promotion has a significant influence on job satisfaction in the village officials of West Seluma Sub-district, Seluma Regency. This means that the increasing positionspromotion, job satisfaction will also increase. The work environment has a significant influence on job satisfaction in the village officials of West Seluma Sub-district, Seluma Regency. This illustrates that the more comfortable work environment is, the job satisfaction of village officials will increase.